Temperature dependence of lattice parameters of SBN single crystals in the vicinity of their structural phase transitions. Issue 7 (3rd July 2013) - Paszkowski, R.; Wokulska, K.; Łukasiewicz, T.; Dec, J.
<x xml:space="preserve">Abstract</x> Changes of lattice parameters of SrxBa1‐xNb2O6 (0.35<x<0.72) solid solution single crystals were measured as a function of temperature. The X‐ray Bond method was used to carry out very precise measurements of the lattice parameters. Fine correlations between values of the lattice parameter and the Sr concentration in the solid solution of SrxBa1‐xNb2O6 single crystals are found. A conventional analysis of lattice parameter data in terms of spontaneous strain and strain/order parameter coupling shows that a normal… <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>